A Masterpiece from the Subprime Mortgage Crisis in America: Subprime mortgage crisis - Radiany, Muhammad Andri; Farhan, Ali; Sumaryono, Roy; Harjanti, Wulandari (International Journal of Scientific Research and Management (IJSRM), 2020)
Subprime mortgage crisis is a phenomenon that has a major impact on the world economy. The crisis that began in the United States has infected many other economically related countries with the United States. This study tries to parse how the economic conditions of the United States in the era before and after the crisis. From the results of the descriptive statistical analysis test on the economic conditions of the United States in the period 1998 - 2017, it was found that in the variables of inflation, investment, GDP, and interest rates there were negative differences between before and after the crisis, even though statistically did not show a significant effect, except for interest rate variable. This phenomenon shows that monetary policy oriented to controlling interest has the potential to trigger systemic risks to the economy.